A Mild, Room-Temperature Protection of Ketones and Aldehydes as 1,3-Dioxolanes under Basic Conditions - Hassner, Alfred; Bandi, Chennakesava Reddy; Panchgalle, Sharad (Synlett, 2012)
Protection of ketones or aldehydes as 1,3-dioxolane derivatives proceeds within minutes at room temperature in the presence of N-hydroxybenzenesulfonamide, its O-benzyl derivative, or the tosyl analogue, in the absence of strong protonic acids, and in the presence of base (Et3N). Acid-sensitive groups such as O-THP, O-TBS, or N-Boc are unaffected.
Keywords: ketals; protecting groups; synthetic methods; ketones; aldehydes